Design and Development of Ant Colony System Algorithms for Block-Based DCT Watermarking - Kannicha Pokudom; Yuttapong Rangsanseri (My University, 2013)
In DCT-based image watermarking, the optimal embedding of the watermark into some of the selected coefficients should depend both on the image content and the trade-off between watermark imperceptibility and watermark robustness. To deal with the image content, an image block classification was applied on each 8 × 8 DCT block. For each region type, Ant Colony System Algorithms were designed and developed to search for the optimal trade-off between watermark imperceptibility and watermark robustness. The resulting optimal frequency bands and embedding strength for watermark embedding were therefore dependent on the region type. The experimental results show that the proposed scheme yielded a watermark that was invisible and robust against various image manipulations. The effectiveness of this algorithm was also compared with those of previous studies.
Keywords: Robustness; Advanced Steganography and Watermarking Techniques